Chapter 1: Tino Rangatiratanga - Durie, Mason (Waitangi Revisited, 2005)
Keywords: constitution; government relations; history; kotahitanga; land tenure; marae; nationhood; race relations; self-governance; tiriti o waitangi/treaty of waitangi

Tino rangatiratanga : water under the bridge? - Bargh, Maria (He pūkenga kōrero: a journal of Māori studies, 2007)
Argues that Māori have been actively engaged in practising tino rangatiratanga in various forms even since before the Declaration of Independence ...
Keywords: colonisation; constitution; government; international relations; iwi; kaitiakitanga; sovereignty; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; water rights